Bonding, bridging, & bypassing understanding ethnic politics in diverse societies - Fox, Colm (Oxford University Press, 2024)
"The idea that ethnicity and democracy don't mix is a widely held assumption. Particularly during elections, it is expected that politicians will mobilize ethnic identities such as race, religion, or tribe, thereby polarizing societies and fostering interethnic strife. Media reports in such countries as India, Iraq, Malaysia, Kenya, and Ghana often describe elections as tense struggles for power and domination between opposing ethnic groups. Sensational statements make the headlines, with leaders valorizing their ethnic kin while denigrating other groups. Popular fears are raised and the risk of interethnic violence increases. To explain this dire turn of events, the standard narrative blames politicians for politicizing ethnicity, but it also excuses them, claiming that the temptation to "play the ethnic card" during elections is too great. After all, it is natural and easy for leaders to draw on emotional attachments and to use beloved ethnic symbols, myths, and a belief in a common blood to rally fervent support. Moreover, stoking fear and prejudice toward an outgroup can be even more effective. Political speeches imbued with historical narratives of persecution, economic hardship, and political discrimination at the hands of a malicious other resonate at a far deeper level than the relatively dull details of policies and platforms. Ultimately, ethnicity is seen as a fixed, unidimensional, and inherently divisive force. So should we just assume that politicians will inevitably exploit ethnic bonds and inherent intergroup prejudice in search of electoral victory?"--Provided by publisher.